A fireproof and heat-insulating mica composite material and preparation method thereof

The mica composite material with boron carbide and zirconium disilicide fillers, combined with modified carbon fibers, addresses the flexibility and strength issues of ceramic silicone rubber, providing superior high-temperature resistance and mechanical properties.

CN118421093BActive Publication Date: 2024-12-24SUNWAY PRECISION TECHNOLOGY (GUANGDONG) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410661207.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-27
Publication Date
2024-12-24
Estimated Expiration
2044-05-27

AI Technical Summary

Technical Problem

Existing ceramic silicone rubber materials suffer from poor flexibility, cracking, and deformation under high temperatures, and the addition of ceramic fillers like glass powder can compromise tensile strength and toughness.

Method used

A fireproof and heat-insulating mica composite material is prepared by incorporating boron carbide particles and zirconium disilicide as ceramic fillers, along with surface-grafted rigid dendritic carbon fibers, which form a dense ceramic layer and enhance mechanical properties.

Benefits of technology

The composite material maintains integrity at ultra-high temperatures up to 1800°C for 30 minutes with improved ablation resistance, toughness, and mechanical strength, preventing brittle fracture and deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004859684290000101
    Figure BDA0004859684290000101
  • Figure BDA0004859684290000111
    Figure BDA0004859684290000111
Patent Text Reader

Abstract

The present invention discloses a fireproof and heat-insulating mica composite material and a preparation method thereof, wherein the composite material comprises the following raw material components by weight: 90-100 parts of silicone rubber raw rubber, 5-10 parts of white carbon black, 1-2 parts of hydroxy silicone oil, 5-10 parts of glass powder, 10-20 parts of mica powder, 30-50 parts of ceramic filler, 0.5-1 parts of auxiliary agent, 5-10 parts of modified carbon fiber, and 1-2 parts of vulcanizing agent. Compared with the prior art, the composite material prepared by the present invention adopts boron carbide particles and zirconium disilicide of a certain mass ratio as ceramic filler, and introduces modified carbon fiber to be used in coordination with it, thereby improving the high-temperature stability and toughness of the composite material. The composite material prepared by the present invention can form a ceramic-like high-hardness protective layer under extremely high temperature ablation, can still maintain the overall shape intact and continue to be resistant to high temperature after ablation in an aerobic environment of 1800°C for 30 minutes, and has excellent anti-ablation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone rubber, and in particular to a fireproof and heat-insulating mica composite material and a preparation method thereof. Background Art

[0002] Ceramic silicone rubber is an innovative material with flame retardant properties. It is easy to prepare and has wide adaptability. By adding a certain amount of ceramic filler, flux and vulcanizer to the silicone rubber matrix, the superior elasticity and mechanical properties of silicone rubber can be maintained at room temperature through the vulcanization process. When facing open flames or high temperature environments, the material can be transformed into a self-supporting ceramic body, effectively preventing flame intrusion and achieving flame retardant and fireproof effects. The preparation process is simple and can be mass-produced through existing industrial equipment. Among them, mica as a ceramic filler plays an important role in ceramic composite materials.

[0003] Mica is a climatic aluminum silicate with flake-shaped particles that can maintain this shape even after grinding. Its main chemical components are silicon dioxide and aluminum oxide. It has good tensile and compressive properties, high lubricity and low volume expansion rate, so it is widely selected as a ceramic filler. In ceramic composites, mica particles begin to melt at high temperatures to form a fluid liquid, which fills between the ceramic filler and the SiO2 generated by silicone rubber, playing the role of a connecting "bridge". At higher temperatures, mica particles react eutectically with the components in the composite material to form a large amount of molten liquid phase, which promotes the formation of the ceramic layer and improves the density of the residue. Mica begins to melt at 800°C and produces molten liquid at 900°C, thus playing an important role in promoting ceramicization at high temperatures. Mica plays an irreplaceable role as a ceramic filler in ceramic composites. Through its melting and eutectic reaction at high temperatures, it provides a dense ceramic structure for the composite material, enhances flame retardancy and high-temperature stability, and provides key support for the wide application of composite materials.

[0004] CN116836553A discloses a highly flame-retardant, high-temperature-resistant, ceramic silicone rubber and a preparation method thereof, which comprises the following raw material components in weight percentage: 30-40 parts of methyl vinyl silicone oil, 22-26 parts of gaseous white carbon, 10-15 parts of alumina particle size, 0-1 part of hydrogen-containing silicone oil, 0-1 part of dimethyl silicone oil, 0-1 part of platinum catalyst, 3-6 parts of zirconium oxide, 3-5 parts of organic silicon, 4-7 parts of glass powder, 5-8 parts of mica powder and 6-8 parts of talc powder. The invention adds glass powder inside, so that under high temperature impact, part of the glass ceramic flame retardant functional powder is melted by heat and sealed with the metal wire to form a heat-insulating glass protective layer. The outer glass powder ceramic flame retardant functional powder is melted by heat to form an inorganic glass-like oxygen-isolating layer to protect the inner resin from high-temperature oxidation, and play a role as a skeleton. Finally, a protective layer is formed on the surface of the metal wire that expands and matches the metal, has adjustable color, is anti-oxidation, anti-reduction, acid-base resistant, and highly weather-resistant, to prevent spontaneous combustion at high temperatures and extend its service life. However, the material has poor flexibility and is prone to cracking, breaking, and deformation.

[0005] CN105860536A discloses a flame retardant and fire-resistant ceramic silicone rubber and a preparation method thereof, which is composed of the following raw materials in parts by weight: 100 parts of methyl vinyl silicone rubber, 1-80 parts of silicon dioxide, 0-10 parts of concentrated crosslinking agent, 0-20 parts of structural control agent, 0.1-10 parts of silane coupling agent, 0-10 parts of organic fiber, 0-50 parts of high temperature resistant resin, 1-160 parts of ceramic powder, 1-80 parts of flame retardant, 0-15 parts of auxiliary agent, 0-30 parts of heat resistant agent, 0.000001-0.1 parts of platinum compound according to the number of parts of platinum, and 0.1-5 parts of vulcanizing agent. The flame retardant and fire-resistant ceramic silicone rubber of the invention has excellent mechanical properties and good heat resistance at room temperature, and overcomes the shortcomings of traditional ceramic silicone rubber that the ceramic material has cracks and poor electrical insulation performance due to the addition of a large amount of glass powder. However, the silicone rubber contains a large amount of ceramic powder and flame retardant, which may have a negative impact on tensile strength and toughness. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the present invention provides a fireproof and heat-insulating mica composite material, which not only has excellent anti-ablation performance and can withstand ultra-high temperature of 1800°C for 30 minutes, but also is not prone to brittle fracture and deformation and has good toughness.

[0007] One of the purposes of the present invention is to provide a method for preparing a fireproof and heat-insulating mica composite material, comprising the following steps:

[0008] (1) Add silicone rubber, white carbon black and hydroxy silicone oil in sequence into an internal mixer at a temperature of 130-135°C and a rotation speed of 60-80 r / min and stir for 3-5 minutes until the mixture is uniformly mixed to obtain a mixed rubber;

[0009] (2) Add the mixed rubber in the above step (1) to a double-roll open mill at a temperature of 70-80° C. and a rotation speed of 10-15 r / min, then add glass powder, mica powder, ceramic filler, additives, modified carbon fiber and vulcanizing agent in sequence, and then back-mix until all components are evenly mixed to obtain a remixed rubber for standby use;

[0010] (3) placing the re-mixed rubber in the above step (2) into a mold for compression molding, and then placing the mold into a flat vulcanizer for vulcanization at a temperature of 170-180° C. and a pressure of 10-12 MPa for 10-15 min to obtain a primary vulcanized sample for standby use;

[0011] (4) Place the primary vulcanized sample in the above step (3) in a blast drying oven at a temperature of 150-160° C. for vulcanization for 1-2 hours, then raise the temperature to 190-200° C. and continue vulcanization for 3-4 hours to obtain a secondary vulcanized sample for standby use;

[0012] (5) Die-cutting, testing and packaging the secondary vulcanized sample in the above step (4) to obtain a fireproof and heat-insulating mica composite material.

[0013] Preferably, the composition comprises the following components by weight: 90-100 parts of silicone rubber raw rubber, 5-10 parts of white carbon black, 1-2 parts of hydroxy silicone oil, 5-10 parts of glass powder, 10-20 parts of mica powder, 30-50 parts of ceramic filler, 0.5-1 parts of additives, 5-10 parts of modified carbon fiber and 1-2 parts of vulcanizing agent.

[0014] Preferably, the silicone rubber raw rubber is one or more of methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, fluorosilicone rubber, and silicon boron rubber.

[0015] Preferably, the vulcanizing agent is selected from one of tert-butyl perbenzoate, 2,4-dichlorobenzoyl peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide.

[0016] Preferably, the auxiliary agent is zinc oxide.

[0017] Preferably, the mass ratio of the glass powder to the mica powder is 1:1.5-2.

[0018] Preferably, the ceramic-forming filler is a mixture of a carbon source material and zirconium disilicide in a mass ratio of 1:0.5-2.

[0019] Further preferably, the carbon source material is selected from one of boron carbide particles, carbon nanotubes and carbon black.

[0020] Preferably, the modified carbon fiber is a surface-grafted rigid dendritic carbon fiber, and its preparation method comprises the following steps, calculated by weight:

[0021] 50-60 parts of chopped carbon fibers and 100-120 parts of 0.25-0.3 mol / L thionyl chloride N, N-dimethylformamide solution are heated and stirred at 80-85°C for 2-3 hours to obtain a mixed solution A; then, 100-120 parts of 0.15-0.2 mol / L melamine N, N-dimethylformamide solution are added to the mixed solution A, and heated and stirred for 2-3 hours to obtain a mixed solution B; 50-60 parts of 0.2 -0.25mol / L 1,3,5-benzenetricarboxylic acid chloride N,N-dimethylformamide solution is stirred for 0.5-1h to obtain a mixed solution C; finally, 100-120 parts of 0.15-0.2mol / L p-phenylenediamine N,N-dimethylformamide solution are added to the mixed solution C and stirred for 0.5-1h to obtain a crude product; the obtained crude product is rinsed with anhydrous ethanol solution for 2-3 times, and then dried at 80-85°C to obtain a surface-grafted rigid dendritic carbon fiber.

[0022] The second object of the present invention is to provide a fireproof and heat-insulating mica composite material prepared by the above-mentioned preparation method.

[0023] The precipitated silica in the present invention is an inorganic substance with good heat resistance and non-flammable properties. When added to silicone rubber, it can improve the flame retardancy and high temperature stability of the composite material. It has a high surface area and contains a large number of hydroxyl groups on the surface, which can form hydrogen bonds with the silicone rubber molecular chain to enhance the interface bonding force between silica and silicone rubber. Its introduction helps to improve the hardness, tensile strength and modulus of the composite material, and enhances the mechanical properties of the material.

[0024] The low melting point glass powder in the present invention is a hard material. When added to the composite material, it can improve the hardness and compressive strength of the material, enhance durability and load-bearing capacity, and at the same time, promote ceramic reaction at high temperature to form a solid ceramic layer, connect the silicone rubber matrix and other ceramic fillers, and improve the stability and strength of the overall composite material.

[0025] The introduction of zinc oxide in the present invention can promote the formation of a ceramic layer, which helps to improve the ceramic effect of the overall composite material and increase the high temperature resistance and flame retardancy of the material.

[0026] Beneficial effects of the present invention:

[0027] 1. Compared with the prior art, the present invention introduces boron carbide particles and zirconium disilicide as ceramic fillers and adds them to the composite material, thereby improving the ablation resistance and stability of the composite material. At high temperatures, the boron carbide particles undergo a carbon thermal reaction to form a SiC ceramic layer with high hardness and high melting point, which provides stable ablation protection for the material. At the same time, ZrSi2 undergoes a carbon thermal reaction with the boron carbide particles to generate ceramic substances such as SiC and ZrO2, forming a solid ceramic protective layer, which effectively isolates the erosion of the internal material by heat flow and oxygen, and improves the ablation resistance and stability of the composite material. The formation of multiphase ceramics in the composite material and the interaction between different ceramic phases provide thermal stability and mechanical strength for the overall structure. In addition, the boron carbide particles are combined with the silicone rubber matrix and the zirconium disilicide particles to reduce the interaction force between the particles, effectively prevent agglomeration and aggregation, and help form a uniform dispersion system, so that the zirconium element is evenly distributed, which promotes the formation of a ceramic protective layer during the ablation process. Therefore, boron carbide particles and zirconium disilicide are used as ceramic fillers to provide strong high-temperature protection and mechanical support for the composite material, so that the prepared composite material can still maintain its overall morphology intact and continue to be resistant to high temperatures after ablation in an oxygen environment at 1800°C for 30 minutes, and has excellent anti-ablation properties.

[0028] 2. The present invention prepares surface-grafted rigid dendritic carbon fibers by modifying carbon fibers, and introduces them into composite materials for coordinated use with boron carbide particles and ZrSi2, which not only further improves the ablation resistance of the composite materials, but also makes up for the reduction in tensile strength and elongation at break of the composite materials caused by the introduction of ZrSi2, so that the prepared composite materials have excellent toughness, which is beneficial to prolonging the service life of the composite materials. The modified carbon fibers in the composite materials are interspersed in the materials and ablation products in an entangled and disordered manner, which has a fixing effect on the ablation residues, and can effectively promote the formation of a high-strength protective layer on the ablation surface, thereby improving the ablation resistance of the composite materials. The surface-grafted rigid dendritic carbon fibers are introduced into the composite materials to form a dendritic macromolecular network structure, which enhances the interfacial compatibility between the carbon fibers and the silicone rubber matrix, helps to disperse local stress, and slows down the expansion of cracks. At the same time, the dendritic macromolecules fill the gaps in the silicone rubber matrix, reduce the obstruction of the silicone rubber molecular chains, and improve the plastic deformation ability of the silicone rubber when loaded, thereby improving the tensile strength of the composite materials, while also strengthening the overall structure of the composite materials and increasing the tensile resistance. The introduction of modified carbon fiber realizes the synergistic effect among silicone rubber, ZrSi2 and carbon fiber, optimizes the mechanical properties, and makes the prepared composite material have excellent toughness. DETAILED DESCRIPTION

[0029] Parameters for specific chemical substances used, sources.

[0030] Methyl vinyl silicone rubber: colorless to light yellow liquid, purity: 99%, manufacturer: Chongqing Ruiya Biological Co., Ltd., product number: 67762-94-1;

[0031] Precipitated silica: purity: 99%, manufacturer: Hubei Kewode Chemical Co., Ltd., EINECS number: 328-92-3;

[0032] Hydroxy silicone oil: purity: 98%, manufacturer: Hubei Rishengchang New Material Technology Co., Ltd., item number: 58130-04-4;

[0033] Low melting point glass powder: manufacturer is Fussman Technology (Beijing) Co., Ltd., item number: FSM1407130;

[0034] Mica powder: purity: 98%, manufacturer: Hubei Yongkuo Technology Co., Ltd., EINECS number: 215-479-3;

[0035] Chopped carbon fiber: produced by Shenzhen Feige Fiber Material Co., Ltd., model: 3mm;

[0036] Boron carbide particles: black particles, produced by Wuhan Xinxin Jiali Biotechnology Co., Ltd., item number: 0354;

[0037] Zirconium disilicide: white solid, purity: 99%, produced by Hubei Chengfeng Chemical Co., Ltd., EINECS number: 234-911-1;

[0038] Melamine: white solid, purity: 99%, produced by Hubei Wonder Chemical Co., Ltd., item number: WD0533;

[0039] Carbon nanotubes: purity: 99%, manufacturer: Hubei Jusheng Technology Co., Ltd., item number: JS3420;

[0040] Carbon black: purity: 99%, manufacturer is Hubei Jiangmin Taihua Chemical Co., Ltd., EINECS number: 215-609-9.

[0041] Example 1

[0042] A method for preparing a fireproof and heat-insulating mica composite material comprises the following steps:

[0043] (1) 100 kg of methyl vinyl silicone rubber, 10 kg of precipitated silica, and 1 kg of hydroxy silicone oil were sequentially added into an internal mixer at a temperature of 133° C. and a rotation speed of 75 r / min, and stirred for 5 min until the mixture was uniform, to obtain a rubber mixture;

[0044] (2) Add the mixed rubber in the above step (1) into a double-roll open mill at a temperature of 75° C. and a rotation speed of 15 r / min, then add 5 kg of low-melting point glass powder, 10 kg of mica powder, 45 kg of porcelain filler, 0.5 kg of zinc oxide, 10 kg of modified carbon fiber and 1 kg of di-tert-butyl peroxide in sequence, and then back-mix until the components are evenly mixed to obtain a remixed rubber for standby use;

[0045] (3) placing the re-mixed rubber in the above step (2) into a mold for compression molding, and then placing the mold into a flat vulcanizer for vulcanization at a temperature of 175° C. and a pressure of 10 MPa for 12 min to obtain a primary vulcanized sample for standby use;

[0046] (4) Place the primary vulcanized sample in the above step (3) in a blast drying oven at a temperature of 150° C. for vulcanization for 1.5 h, then raise the temperature to 200° C. and continue vulcanization for 3.5 h to obtain a secondary vulcanized sample for later use;

[0047] (5) Die-cutting, testing and packaging the secondary vulcanized sample in the above step (4) to obtain a fireproof and heat-insulating mica composite material.

[0048] The ceramic filler is formed by mixing 22.5 kg of boron carbide particles and 22.5 kg of zirconium disilicide.

[0049] The modified carbon fiber is a surface-grafted rigid dendritic carbon fiber, and the preparation method thereof comprises the following steps:

[0050] 50g of chopped carbon fiber and 100g of 0.25mol / L thionyl chloride N,N-dimethylformamide solution were heated and stirred at 80°C for 3h to obtain a mixed solution A; then, 100g of 0.15mol / L melamine N,N-dimethylformamide solution was added to the mixed solution A, and the mixture was heated and stirred for 3h to obtain a mixed solution B; 50g of 0.2mol / L 1,3,5-benzenetricarborate chloride N,N-dimethylformamide solution was added to the mixed solution B, and the mixture was stirred for 1h to obtain a mixed solution C; finally, 100g of 0.15mol / L p-phenylenediamine N,N-dimethylformamide solution was added to the mixed solution C, and the mixture was stirred for 1h to obtain a crude product; the obtained crude product was rinsed twice with anhydrous ethanol solution, and then dried at 80°C to obtain a surface-grafted rigid dendritic carbon fiber.

[0051] Example 2

[0052] A method for preparing a fireproof and heat-insulating mica composite material, which differs from Example 1 in that the ceramic filler is a mixture of 22.5 kg of carbon nanotubes and 22.5 kg of zirconium disilicide.

[0053] The preparation method of the modified carbon fiber is consistent with that of Example 1.

[0054] Example 3

[0055] A method for preparing a fireproof and heat-insulating mica composite material, which differs from Example 1 in that the ceramic filler is a mixture of 22.5 kg of carbon black and 22.5 kg of zirconium disilicide.

[0056] The preparation method of the modified carbon fiber is consistent with that of Example 1.

[0057] Example 4

[0058] A method for preparing a fireproof and heat-insulating mica composite material, which differs from Example 1 in that the ceramic filler is a mixture of 15 kg of boron carbide particles and 30 kg of zirconium disilicide.

[0059] The preparation method of the modified carbon fiber is consistent with that of Example 1.

[0060] Example 5

[0061] A method for preparing a fireproof and heat-insulating mica composite material, which differs from Example 1 in that the ceramic filler is a mixture of 30 kg of boron carbide particles and 15 kg of zirconium disilicide.

[0062] The preparation method of the modified carbon fiber is consistent with that of Example 1.

[0063] Comparative Example 1

[0064] A method for preparing a fireproof and heat-insulating mica composite material, which differs from Example 1 in that the ceramic filler is 45 kg of zirconium disilicide.

[0065] The preparation method of the modified carbon fiber is consistent with that of Example 1.

[0066] Comparative Example 2

[0067] A method for preparing a fireproof and heat-insulating mica composite material comprises the following steps:

[0068] (1) 100 kg of methyl vinyl silicone rubber, 10 kg of precipitated silica, and 1 kg of hydroxy silicone oil were sequentially added into an internal mixer at a temperature of 133° C. and a rotation speed of 75 r / min, and stirred for 5 min until the mixture was uniform, to obtain a rubber mixture;

[0069] (2) Add the mixed rubber in the above step (1) into a two-roll open mill at a temperature of 75° C. and a rotation speed of 15 r / min, then add 5 kg of low-melting point glass powder, 10 kg of mica powder, 45 kg of porcelain-forming filler, 0.5 kg of zinc oxide and 1 kg of di-tert-butyl peroxide in sequence, and then back-mix until all components are evenly mixed to obtain a remixed rubber for standby use;

[0070] (3) placing the re-mixed rubber in the above step (2) into a mold for compression molding, and then placing the mold into a flat vulcanizer for vulcanization at a temperature of 175° C. and a pressure of 10 MPa for 12 min to obtain a primary vulcanized sample for standby use;

[0071] (4) Place the primary vulcanized sample in the above step (3) in a blast drying oven at a temperature of 150° C. for vulcanization for 1.5 h, then raise the temperature to 200° C. and continue vulcanization for 3.5 h to obtain a secondary vulcanized sample for later use;

[0072] (5) Die-cutting, testing and packaging the secondary vulcanized sample in the above step (4) to obtain a fireproof and heat-insulating mica composite material.

[0073] The ceramic filler is formed by mixing 22.5 kg of boron carbide particles and 22.5 kg of zirconium disilicide.

[0074] Test Example 1

[0075] Ablation resistance test

[0076] Referring to the standard of GJB 323A-1996 Ablation Test Method for Ablative Materials, the oxygen-acetylene ablation test method was selected to perform ablation tests on the composite materials prepared in Examples 1-5 and Comparative Example 1. The ablation time was 20 s. The linear ablation rate (R l ) and mass ablation rate (R m ). l and R m Calculate according to the following formula (1) and formula (2) respectively.

[0077] Formula (1): R l =(d1-d2) / t

[0078] Formula (2): R m =(m1-m2) / t

[0079] In formula (1), d1 is the original thickness of the sample (mm), d2 is the thickness after ablation (mm), and t is the ablation time (s);

[0080] In formula (2), m1 is the original mass of the sample (g), m2 is the mass after ablation (g), and t is the ablation time (s).

[0081] The composite materials prepared in Examples 1-5 and Comparative Example 1 were ablated in an oxygen environment at 1800° C. for 30 min, and the ceramic layer and overall morphology of each composite material were observed and recorded.

[0082] The test details are shown in Table 1.

[0083] Table 1 Test results of product anti-ablation performance

[0084]

[0085] As shown in Table 1, compared with Examples 1-5 and Comparative Example 1, the linear ablation rate and mass ablation rate of Examples 1-5 are lower than those of Comparative Example 1, and after ablation in an oxygen environment at 1800°C for 30 minutes, the ceramic layers of Examples 1-5 are dense and hard, while the ceramic layer of Comparative Example 1 becomes loose, indicating that the ablation resistance of Examples 1-5 is better than that of Comparative Example 1, and the ablation resistance of Example 1 is the best. The reason for this may be that boron carbide particles and zirconium disilicide (ZrSi2) are added to the composite material as ceramic fillers. At high temperatures, the boron carbide particles undergo a carbon thermal reaction to form a SiC ceramic layer with high hardness and high melting point, providing stable ablation protection for the material. At the same time, ZrSi2 undergoes a carbon thermal reaction with the boron carbide particles to generate ceramic substances such as SiC and ZrO2, forming a solid ceramic protective layer, which effectively isolates the erosion of the internal material by heat flow and oxygen, and improves the ablation resistance and stability of the composite material. The formation of multiphase ceramics in the composite material and the interaction between different ceramic phases provide thermal stability and mechanical strength for the overall structure. In addition, the boron carbide particles are combined with the silicone rubber matrix and zirconium disilicide particles to reduce the interaction force between the particles, effectively prevent agglomeration and aggregation, help form a uniform dispersion system, make the zirconium element evenly distributed, and promote the formation of a ceramic protective layer during the ablation process. At the same time, the modified carbon fibers in the composite material have a fixing effect on the ablation residues by interweaving disorderly in the material and the ablation product, just like the effect of vegetation on the soil, which increases the yield of carbon residues, effectively promotes the formation of a high-strength protective layer on the ablation surface, and further improves the ablation resistance of the composite material. Therefore, by using boron carbide particles, ZrSi2 and modified carbon fibers in a coordinated manner and optimizing the mixing ratio, the composite material is provided with strong high-temperature protection and mechanical support, so that the prepared composite material can still maintain the overall shape integrity and continue to be resistant to high temperature after ablation in an aerobic environment at 1800℃ for 30 minutes, and has excellent ablation resistance.

[0086] Test Example 2

[0087] Material toughness test

[0088] Tensile properties test

[0089] According to GB / T 528-2009 Test of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, tensile properties of the composite materials prepared in Examples 1-5 and Comparative Example 2 were tested. The test specimens were dumbbell type I, 5 specimens were tested in each group, and the test results were averaged.

[0090] The specific test results are shown in Table 2.

[0091] Table 2 Product toughness test results

[0092]

[0093] As shown in Table 2, compared with Example 1-5 and Comparative Example 2, the tensile strength and elongation at break of Example 1-5 are significantly higher than those of Comparative Example 2, indicating that the tensile properties of Example 1-5 are better than those of Comparative Example 2, and the tensile properties of Example 1 are the best, indicating that the introduction of ZrSi2 will cause the tensile strength and elongation at break of the composite material to decrease, and the introduction of modified carbon fiber can well make up for this defect, so that the prepared composite material has excellent toughness, which is conducive to extending the service life of the composite material. The reason for the analysis may be that ZrSi2 destroys the continuity of the silicone rubber matrix, forms a dispersed hard phase, increases the possibility of local stress concentration, promotes the occurrence and expansion of cracks, thereby reducing the tensile strength of the material as a whole. And the introduction of ZrSi2 particles may hinder the movement of silicone rubber molecular chains, causing silicone rubber to be more difficult to plastically deform when loaded, reducing the tensile strength of the composite material. The reduction in tensile strength and the reduction in elongation at break make the composite material more prone to brittle fracture under tensile loading, reducing the toughness of the material.

[0094] By introducing surface-grafted rigid dendritic carbon fibers, a dendritic macromolecular network structure is formed in the composite material. These macromolecules form physical entanglements on the carbon fiber surface and are more tightly connected to the silicone rubber matrix through strong interface bonding. The effect of this introduction helps to disperse local stress, slow down the expansion of cracks, resist the brittle fracture of the composite material when loaded, and improve the toughness of the overall composite material. At the same time, the dendritic macromolecules fill the gaps in the silicone rubber matrix, reduce the obstruction of the silicone rubber molecular chain, and improve the plastic deformation ability of the silicone rubber when loaded, thereby improving the tensile strength of the composite material. At the same time, it also strengthens the overall structure of the composite material, increases the tensile resistance, helps to make up for the weaknesses caused by the introduction of ZrSi2 in the silicone rubber matrix, and improves the overall tensile strength. The introduction of modified carbon fibers achieves the synergistic effect between silicone rubber, ZrSi2 and carbon fibers, optimizes the mechanical properties, and makes the prepared composite material have excellent toughness.

Claims

1. A method for preparing a fireproof and heat-insulating mica composite material, characterized in that: The following steps are involved: (1) Add silicone rubber, white carbon black and hydroxy silicone oil in sequence into an internal mixer at a temperature of 130-135°C and a rotation speed of 60-80 r / min and stir for 3-5 minutes until the mixture is uniformly mixed to obtain a mixed rubber; (2) Add the mixed rubber in the above step (1) to a double-roll open mill at a temperature of 70-80° C. and a rotation speed of 10-15 r / min, then add glass powder, mica powder, ceramic filler, additives, modified carbon fiber and vulcanizing agent in sequence, and then back-mix until all components are evenly mixed to obtain a remixed rubber for standby use; (3) placing the re-mixed rubber in the above step (2) into a mold for compression molding, and then placing the mold into a flat vulcanizer for vulcanization at a temperature of 170-180° C. and a pressure of 10-12 MPa for 10-15 min to obtain a primary vulcanized sample for standby use; (4) Place the primary vulcanized sample in the above step (3) in a blast drying oven at a temperature of 150-160° C. for vulcanization for 1-2 hours, then raise the temperature to 190-200° C. and continue vulcanization for 3-4 hours to obtain a secondary vulcanized sample for standby use; (5) die-cutting, testing and packaging the secondary vulcanized sample in the above step (4) to obtain a fireproof and heat-insulating mica composite material; The raw materials, by weight, are as follows: 90-100 parts of silicone rubber, 5-10 parts of white carbon black, 1-2 parts of hydroxy silicone oil, 5-10 parts of glass powder, 10-20 parts of mica powder, 30-50 parts of porcelain filler, 0.5-1 parts of additives, 5-10 parts of modified carbon fiber, and 1-2 parts of vulcanizing agent; The ceramic filler is a mixture of carbon source material and zirconium disilicide in a mass ratio of 1:0.5-2; The carbon source material is boron carbide particles; The modified carbon fiber is a surface-grafted rigid dendritic carbon fiber, and its preparation method comprises the following steps, calculated by weight: 50-60 parts of chopped carbon fibers and 100-120 parts of 0.25-0.3 mol / L thionyl chloride N, N-dimethylformamide solution are heated and stirred at 80-85°C for 2-3 hours to obtain a mixed solution A; then, 100-120 parts of 0.15-0.2 mol / L melamine N, N-dimethylformamide solution are added to the mixed solution A, and heated and stirred for 2-3 hours to obtain a mixed solution B; 50-60 parts of 0.2 -0.25mol / L 1,3,5-benzenetricarboxylic acid chloride N,N-dimethylformamide solution is stirred for 0.5-1h to obtain a mixed solution C; finally, 100-120 parts of 0.15-0.2mol / L p-phenylenediamine N,N-dimethylformamide solution are added to the mixed solution C and stirred for 0.5-1h to obtain a crude product; the obtained crude product is rinsed with anhydrous ethanol solution for 2-3 times, and then dried at 80-85°C to obtain a surface-grafted rigid dendritic carbon fiber.

2. The method for preparing the fireproof and heat-insulating mica composite material according to claim 1, characterized in that: The silicone rubber raw rubber is one or more of methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, fluorosilicone rubber and silicon boron rubber.

3. The method for preparing the fireproof and heat-insulating mica composite material according to claim 1, characterized in that: The vulcanizing agent is selected from one of tert-butyl perbenzoate, 2,4-dichlorobenzoyl peroxide, di-tert-butyl peroxide and diisopropylbenzene peroxide.

4. The method for preparing the fireproof and heat-insulating mica composite material according to claim 1, characterized in that: The auxiliary agent is zinc oxide.

5. The method for preparing the fireproof and heat-insulating mica composite material according to claim 1, characterized in that: The mass ratio of the glass powder to the mica powder is 1:1.5-2.

6. A fireproof and heat-insulating mica composite material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.